2016
DOI: 10.1177/0897190016679759
|View full text |Cite
|
Sign up to set email alerts
|

Provider Perception of Pharmacy Services in the Patient-Centered Medical Home

Abstract: Top-tier clinical, cost/access, and educational services considered worthwhile by providers in a PCMH have been identified. In addition to these services, when developing or evaluating a pharmacy service, special attention should be paid to provider preference for physical location in the office and perceived barriers to the pharmacist availability, concern over complex disease management competency and patient confusion as to the role of the pharmacist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Similar to the current study, several studies showed that a lack of understanding and awareness, and resistance among the patients, were barriers to implementation of CPS [ 24 , 30 , 69 ]. Two studies reported that the pharmacist should assume a proactive role in the pharmacist-patient relationship [ 70 , 71 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar to the current study, several studies showed that a lack of understanding and awareness, and resistance among the patients, were barriers to implementation of CPS [ 24 , 30 , 69 ]. Two studies reported that the pharmacist should assume a proactive role in the pharmacist-patient relationship [ 70 , 71 ].…”
Section: Discussionsupporting
confidence: 79%
“…The lack of adequate physical structures in the health units was a barrier to the implementation of CPS. Structural problems can impact on the quality of care provided, the privacy required to perform CPS, and the construction of a therapeutic relationship between the pharmacist and their patients [ 11 , 24 , 25 ]. In Brazil, there is legislation that regulates the provision of adequate physical structures.…”
Section: Discussionmentioning
confidence: 99%
“…28 , 29 A similar survey distributed to providers within a PCMH identified top-tier clinical services as medication counseling, reconciliation, adherence assessment, polypharmacy assessment, and drug information consultations. 30 Of note, pain management was only reported to be offered in 35% of the practices but was ranked as one of the most impactful in our study. Our data can help guide clinical pharmacists to tailor their services to best fit the needs of their practice site.…”
Section: Discussionmentioning
confidence: 65%
“…Similarly, some studies show that one of the main difficulties in this process is to reconcile clinical and logistic activities. [ 84 , 87 , 98 ]. For Garcia-Cardenas et al [ 25 ], several factors can contribute to the lack of time, such as lack of priority, commitment, and poor distribution of activities.…”
Section: Discussionmentioning
confidence: 99%